Reforma a la Ley Orgánica De Transporte Terrestre, Tránsito Y Seguridad Vial en cuanto a las sanciones establecidas a los delitos de tránsito - Carrión Jiménez, Vicente Iván (2016)
The importance and importance of the Partner-Legal problem under the title “REFORMS TO THE STATUTORY LAW OF TERRESTRIAL TRANSPORT, TRANSIT AND ROAD SECURITY TO SANCTION WITH MORE DRASTICIDAD THE INFRACTIONS THAN COMMIT THE CONDUCTORS BY IMPRUDENCE, SKILL, NEGLIGENCE AND FAILURE OF THE LAW” are based mainly on the necessity to help in the reduction of the index of economic loss and traffic accidents that nowadays has become great a problematic one by the deaths that cause this type of infractions and that the administration of Ecuadorian justice is itself forced by the weakness of the sanctions within the legal body, although the Constitution of the Republic of Ecuador, guarantees the right to the life and the legal security, same that must be respected and be applied of coherent and systematic form, otherwise would not be more than enunciated legal than they would be in dead letter and a vain lyricism that our State like one boasts of the best Constitutions, is thus, that the violation to this right, harms most important rights consecrated in our Constitution. I make emphasis that the sanctions anticipated in the Statutory law of Terrestrial Transport Transit and Road Security in Ecuador are inconsistences reason why several conductors little recklessness have to him to the sanctions which puts in risk human lives and goods. Problematic the legal one to that it is had made reference in previous lines is studied in this one investigative work which concludes with a proposal of legal reform with which it is tried to punish with pertinent severity to the violators with the intention of guaranteeing the constitutional rights and of international treaties, reforming the Statutory law of Terrestrial Transport, Transit and Road Security, in its opportune part so that it is agreed with the Constitution that is the supreme norm that must prevail. In the development of the Thesis, one was that indeed people exist who evade such responsibility occurring to the flight, which means great loss for the part affected without being able to clarify the culpability and to sanction of correct form. In other cases the causes do not happen of the Previous Investigation and soon they are filed, and in few occasions the part is arrived to dictate to somewhat weak sentence but in the disposition on the part of the judges occurring more pecuniary sanctions and few punitive ones. In aim in this thesis manifest the great existing preoccupation by the citizenship who have undergone east type of accidents and that in their majority have been left in impunity these causes, and others do not transact them because they consider that the culprit is not punished properly